2019
DOI: 10.1080/09537287.2019.1695912
|View full text |Cite
|
Sign up to set email alerts
|

Environmental behaviour and choice of sustainable travel mode in urban areas: comparative evidence from commuters in Asian cities

Abstract: Promoting pro-environmental travel modes is an important strategy for sustainable transportation. Previous studies have shown a positive relationship between environmental awareness and environmentally friendly travel modes, but very few studies have considered pro-environmental behaviour and choice of travel mode, particularly in the context of non-Western countries. This study examines the impact of pro-environmental behaviour on the choice of commuting mode in Tokyo, Beijing, Shanghai and Singapore using or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(80 reference statements)
2
5
2
Order By: Relevance
“…This might be because the Center district and East district are urban areas with quality cycling infrastructure and greater street network connectivity than the other districts [ 56 ]. Moreover, household type has no significant relationship with bicycle commuting in this study, which is in contrast with the results of Kumagai and Managi [ 41 ] who conducted a survey in Beijing and Singapore.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This might be because the Center district and East district are urban areas with quality cycling infrastructure and greater street network connectivity than the other districts [ 56 ]. Moreover, household type has no significant relationship with bicycle commuting in this study, which is in contrast with the results of Kumagai and Managi [ 41 ] who conducted a survey in Beijing and Singapore.…”
Section: Discussioncontrasting
confidence: 99%
“…Stern [ 50 ] also put forward a similar point of view that some environmental behaviors may follow from a desire to save money. These results are in contrast with Kumagai and Managi [ 41 ], who indicated that environmental behaviors taken at home have a significant relationship with bicycle commuting in Beijing. However, PB (β = 0.22) is positively correlated with bicycle commuting.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The findings suggest that a high level of environmental awareness exerts a positive effect on the use of more environmentally friendly transport modes. Such findings are in accordance withconsistent to those of previous studies (Gardner and Abraham, 2010;Kumagai and Managi, 2019;Lind et al 2015;Liu et al, 2017;Mei et al, 2017;Xu et al, 2020;Zhou et al, 2020).…”
Section: Environmental Awarenesssupporting
confidence: 94%